Kajian Pelaksanaan Program Penanggulangan Tuberkulosis Paru di Wilayah Kerja Puskesmas Sikumana Kota Kupang Tahun 2022 - Arche E.E Taneo; Dominirsep O. Dodo; Mega O.L Liufeto (Yayasan Literasi Sains Indonesia, 2025)
Tuberculosis (TB) is one of the most dangerous infectious diseases in the world and is among the top ten causes of death globally. This study aims to analyze the implementation of the pulmonary TB control program at the Sikumana Health Center, Kupang City, in 2022. This research employs a descriptive qualitative method through interviews selected based on purposive sampling. The results indicate that in terms of input, human resources and funding are sufficient, but infrastructure remains inadequate. Regarding the process, program planning is conducted by a special team in collaboration with the head of the health center and healthcare workers during a cross-sectoral mini-workshop. The Sikumana Health Center collaborates with sub-district heads, village heads, health cadres, PMOs, and the military (Babinsa) to monitor medication adherence and track TB contact patients. Case detection is carried out actively and passively, with diagnosis conducted through a Molecular Rapid Test (TCM). The treatment follows the 2016 pulmonary TB control guidelines, while recording and reporting activities are done both manually and electronically. The main challenges include treatment dropout due to patient mobility, low public awareness of TB control, limited cross-sectoral involvement, and an increased workload for analysts due to extensive contact tracing. In conclusion, while the program is running well, several obstacles need to be addressed to enhance the effectiveness of pulmonary TB control at the Sikumana Health Center.